Biological Effects and Crystal X-Ray Study of Novel Schiff Base Containing Pentafluorophenyl Hydrazine: In Vitro and in Silico Studies - Hamurcu, Fatma; Ozmen, Ummuehan Ozdemir; Senturk, Ozan Sanli; Kaya, Kerem; Adem, Sevki; Erden, Buesra Aksoy; Çelebioğlu, Hasan Ufuk; Çelebioğlu, Hasan Ufuk; Hamurcu, Fatma; Erden, Büşra Aksoy (Wiley-V C H Verlag Gmbh, 2023)
A novel Schiff base namely 3,5-di-tert-butyl-6-((2-(perfluorophenyl)hydrazono)methyl)phenol was successfully synthesized and characterized using FT-IR and 1H-NMR, 13C-NMR, and 19F-NMR. The crystal structure analysis of the Schiff base compound was also characterized with single crystal X-ray diffraction studies and supported the spectroscopic results. The cytotoxicity, anti-bacterial properties, and enzyme inhibition of the compound were also investigated. The molecular docking studies were performed in order to explain the interactions of the synthesized compound with target enzymes. The newly synthesized hydrazone derivative Schiff base compound showed high cellular toxicity on MCF-7 and PC-3 cells. Also, this compound caused low antibacterial effect on E. coli and S. aureus. Besides, the compound exhibited the inhibitory effect against pancreatic cholesterol esterase and carbonic anhydrase isoenzyme I, II with IC50 values 63, 99, and 188 mu M, respectively. Consequently, it has been determined that the prepared Schiff base is an active compound in terms of cytotoxicity, enzyme inhibition, and anti-bacterial properties. These results provide preliminary information for some biological features of the compound and can play a major role in drug applications of the Schiff base compound.
Keywords: Schiff Base; Hydrazone; Anticancer; Enzyme Inhibition; Antibacterial Activity Molecular Docking